(untitled) (Dhaka University Journal of Biological Sciences, 2021)
An experiment was conducted to investigate the effect of aluminium (Al) toxicity on the anatomical changes in the root, stem and leaf of chickpea (Cicer arietinum L.) plants grown in sand culture. Toxicity of Al reduced the length of primary root and the number of lateral roots of chickpea than that of the control. Aluminium decreased the size and number of vessels in the root of chickpea. Larger area of sclerenchyma cells was noticed in the stem of Al-stressed plant. Number of palisade parenchyma was reduced in the leaf of chickpea. Aluminium treatment caused closure of stomata. Increased number of trichomes in chickpea leaves was also reported due to aluminium. Dhaka Univ. J. Biol. Sci. 30(2): 187-196, 2021 (July)